Fish Energy Use among Fluctuating and Constant Thermal Regimes Simulating Winter Conditions in Rivers. Issue 5 (12th August 2015) - Hansen, Eriek S.; Rahel, Frank J.
Abstract: During the winter, variation in water temperature in temperate‐zone rivers is strongly influenced by the presence or absence of surface ice cover. Prior to ice formation, water temperatures can fluctuate from nighttime lows near 0°C to daytime highs near 6°C. After ice formation, temperatures remain constant near 0°C. Climate change is projected to reduce the duration of surface ice cover in aquatic ecosystems and, thus, alter winter temperature regimes. We conducted a laboratory experiment to compare fish energy use for two situations: (1) ice free conditions with diel cycling temperatures (0.2–6°C), and (2) ice cover conditions with constant low temperatures (0.5°C). We compared the response of Creek Chub Semotilus atromaculatus, representing a coolwater species, and Brook Trout Salvelinus fontinalis, representing a coldwater species, to these temperature regimes. During a 60‐d study we monitored metabolic measurements of energy use and proximate body composition of fasted fish. For Creek Chub, there was no effect of time or temperature regime on respiration rates. Ammonium excretion declined over time for Creek Chub held at the constant low temperature but remained unchanged for fish held at the cycling temperature. For Brook Trout, there was no effect of time or temperature regime on respiration or ammonium excretion. Both species showed a loss of body lipids over the 60 d but there was no difference in the rate of loss between the two temperature treatments. Thus, we were unable to detect a difference in the energy use for these species between the different thermal regimes simulating the presence or absence of surface ice cover.